High Intensity Focused Ultrasound (20 MHz) and Cryotherapy as Therapeutic Options for Granuloma Annulare and Other Inflammatory Skin Conditions - Jacek Calik; Tomasz Zawada; Natalia Sauer; Torsten Bove (Adis, Springer Healthcare, 2024)
Abstract Introduction In dermatology, inflammatory skin conditions impose a substantial burden worldwide, with existing therapies showing limited efficacy and side effects. This report aims to compare a novel immunological activation induced by hyperthermic 20 MHz high intensity focused ultrasound (HIFU) with conventional cryotherapy. The bioeffects from the two methods are initially investigated by numerical models, and subsequently compared to clinical observations after treatment of a patient with the inflammatory disease granuloma annulare (GA). Methods Clinical responses to moderate energy HIFU and cryotherapy were analysed using numerical models. HIFU-induced pressure and heat transfer were calculated, and a three-layer finite element model simulated temperature distribution and necrotic volume in the skin. Model output was compared to 22 lesions treated with HIFU and 10 with cryotherapy in a patient with GA. Results Cryotherapy produced a necrotic volume of 138.5 mm3 at − 92.7 °C. HIFU at 0.3-0.6 J/exposure and focal depths of 0.8 or 1.3 mm generated necrotic volumes up to only 15.99 mm3 at temperatures of 68.3-81.2 °C. HIFU achieved full or partial resolution in all treated areas, confirming its hyperthermic immunological activation effect, while cryotherapy also resolved lesions but led to scarring and dyspigmentation. Conclusion Hyperthermic immunological activation of 20 MHz HIFU shows promise for treating inflammatory skin conditions as exemplified by GA. Numerical models demonstrate minimal skin necrosis compared to cryotherapy. Suggested optimal HIFU parameters are 1.3 mm focal depth, 0.4-0.5 J/exposure, 1 mm spacing, and 1 mm margin. Further studies on GA and other inflammatory diseases are recommended.